2014
DOI: 10.1002/2013jf002958
|View full text |Cite
|
Sign up to set email alerts
|

Variable deceleration of Whillans Ice Stream, West Antarctica

Abstract: The Whillans Ice Stream Ice Plain (WIP) has been slowing since at least 1963. Prior constraints on this slowdown were consistent with a constant long-term deceleration rate. New observations of ice velocity from 11 continuous and 3 seasonal GPS sites indicate the deceleration rate varies through time including on interannual time scales. Between 2009 and 2012 WIP decelerated at a rate (6.1 to 10.9 ± 2 m/yr 2 ) that was double the multidecadal average (3.0 to 5.6 ± 2 m/yr 2 ). To identify the causes of slowdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 43 publications
10
49
0
Order By: Relevance
“…Both of these processes have been confirmed by field-studies on present day Antarctic ice streams (Engelhardt et al, 1990;Engelhardt and Kamb, 1997;Engelhardt and Kamb, 1998;Kamb, 2001). Furthermore, spatial and temporal variations in the availability of subglacial meltwater are known to occur (Gray et al, 2005;Murray et al, 2008;Vaughan et al, 2008) and re-routing of meltwater has been suggested to cause speedup, slowdown, or stagnation of ice streams in Antarctica Anandakrishnan and Alley, 1997;Anandakrishnan et al, 2001;Wright et al, 2008;Beem et al, 2014). Surface melt-induced speed-up of ice streams in Greenland has also been hypothesised (Zwally et al, 2002;Parizek and Alley, 2004;Bartholomew et al, 2010), but the precise response of the subglacial drainage system is not always straightforward (Schoof, 2010;Sundal et al, 2011;Meierbachtol et al, 2013).…”
Section: Meltwater At the Bedmentioning
confidence: 81%
See 1 more Smart Citation
“…Both of these processes have been confirmed by field-studies on present day Antarctic ice streams (Engelhardt et al, 1990;Engelhardt and Kamb, 1997;Engelhardt and Kamb, 1998;Kamb, 2001). Furthermore, spatial and temporal variations in the availability of subglacial meltwater are known to occur (Gray et al, 2005;Murray et al, 2008;Vaughan et al, 2008) and re-routing of meltwater has been suggested to cause speedup, slowdown, or stagnation of ice streams in Antarctica Anandakrishnan and Alley, 1997;Anandakrishnan et al, 2001;Wright et al, 2008;Beem et al, 2014). Surface melt-induced speed-up of ice streams in Greenland has also been hypothesised (Zwally et al, 2002;Parizek and Alley, 2004;Bartholomew et al, 2010), but the precise response of the subglacial drainage system is not always straightforward (Schoof, 2010;Sundal et al, 2011;Meierbachtol et al, 2013).…”
Section: Meltwater At the Bedmentioning
confidence: 81%
“…An illustration of this might be an inference of Stokes et al (2009) that the quiescence of the M'Clure Strait Ice Stream was caused by its previous rapid retreat into deeper and wider Viscount Melville Sound, which led to a thinning and a subsequent freeze-on of the ice mass (cf. Christoffersen and Tulaczyk, 2003;Beem et al, 2014), and to profound changes in the configuration of the ice sheet sector.…”
Section: Stability Of Ice Drainage Networkmentioning
confidence: 99%
“…Joughin et al [] inverted ice surface velocity measurements to infer bed shear stresses on the WIP and found values 1.3–2.8 kPa, with this range reflecting uncertainty in the model parameterization. However, the study by Joughin et al [] as well as other remote sensing studies [ Beem et al , ; Sergienko et al , ] have also found that bed shear stress on the WIP is heterogeneous, with ∼10 km regions of elevated basal strength as high as ∼30–50 kPa [see, e.g., Joughin et al , , Figure 12]. Because of this heterogeneity, as well as the large distance between the WIP and the UpB site, we consider our estimate of basal shear strength to be consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A change of this magnitude is entirely possible given the uncertainty in basal topography and what is known about thickness fluctuations in these ice streams. Kamb Ice Stream stagnated around 150 years ago [Catania et al, 2012], and Whillans Ice Stream is currently slowing by 1-2% per year, toward a possible stagnation early next century [Beem et al, 2014]. In response to these dynamical changes, Kamb has thickened and the southern Whillans Ice Plain and Mercer Ice Stream have experienced overall thinning over the last 60 years [Winberry et al, 2014].…”
Section: Subglacial Hydrologymentioning
confidence: 99%